Applying Marketing Strategies to Add Value to Peasant Paintings in Northern Guangxi Province, People's Republic of China: Applying Marketing Strategies to Add Value to Peasant Paintings in Northern Guangxi Province, People's Republic of China - Huaiyu, Wen; Sodphiban, Pichai (RATANABUTH JOURNAL, 2026)
This study aimed to: 1) examine the history, characteristics, and cultural value of peasant folk paintings in northern Guangxi Province, People’s Republic of China; 2) analyze marketing strategies to enhance their value; and 3) develop a marketing-oriented management model to increase their economic and cultural value. A mixed-methods approach was employed, combining documentary research with semi-structured interviews. The sample consisted of 300 participants, including artists, painters, students, and tourists. Data were analyzed using content analysis and descriptive statistics, including mean and standard deviation. The findings revealed that peasant folk paintings in northern Guangxi possess distinctive cultural identities that strongly reflect local ways of life and indigenous wisdom. The application of marketing strategies significantly enhanced the value of these artworks, with overall satisfaction reported at a high level (𝑥̄ = 3.39, SD =1.00). Key strategies included identity-based branding, appropriate pricing, digital media promotion, and the integration of cultural value into the creative economy. The study concludes that integrating marketing strategies with cultural heritage preservation can effectively enhance both the economic and social value of peasant paintings. This approach also provides a sustainable pathway for preserving and transmitting local cultural wisdom to future generations.